Hello pouvez vous n aider....A=3(x-2)+5(3-x).....b=x(3+x)-2(x+5)......c=-2(x-7)-2(x²+x)+4(x²+1)....d=2x(-x+5)-x²(1-x).....e=-6x(2x²-3x)-3(x+4x²)-x(-3+4x)......f=(x+2)(-x-3)+3x²............merci

1
Tu peut donner l'énoncé de ton exo stp ?
Il faut l'énoncé pour savoir x= ?

Réponses

2014-02-07T16:28:24+01:00
Bonjour

a = 2(x - 1) + 2(y + 2) - 2(1 + z)
  = 2x - 2 + 2y + 4 - 2 - 2z
  = 2x + 2y - 2z

b = 3x - (3 - 3y ) + 3(z + 1)
   = 3x - 3 + 3y + 3z + 3
   = 3x + 3y + 3z

c = (x + y -1) + (x + y + 1) - (x + y - z)
   = x + y - 1 + x + y + 1 - x - y + z
   = x + y + z

d = 2(x - y) + 3(y - z) + 4(z - x) + 3x
   = 2x - 2y + 3y - 3z + 4z - 4x + 3x
   = x + y + z

e = x(1 - y) + y(1 - z) + z(1 - x) + xy + yz +xz
   = x - xy + y - yz + z - xz + xy + yz + xz
   = x + y + z

f = (x + 2)(-x - 3) + 3x²
  = -x² - 3x - 2x - 6 + 3x²
  = 2x² - 5x - 6